(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article first examines, from a diachronic and synchronic perspective, the rise and evolution of nicknames, a specific type of names through which it is intended to verify that, despite being a verbalized activity of marginal communities, it includes all the sociocultural levels by intervening various grammatical resources from which a person is identified and defined based on a certain circumstance s/he is linked to. The characteristics, referents, resources of composition and sense are analyzed based on a corpus selected from different cultural segments and, then on a corpus selected from penitentiaries of the central south in Chile, where ingenuity, comicality, sarcasm and restrained secrecy —the reason why they require further explanation— form the basis of the creation of nicknames.